Teaching Literature With Elf Paradigm in Elt Classrooms - Tülüce, Hande Serdar; Altınmakas, Derya (Taylor and Francis, 2023)
This chapter shows how teachers can utilise literary texts in their language classrooms to unearth the potential of the ELF paradigm in promoting general and critical language awareness and preparing students for the complex and diversified socio-linguistic reality of the 21st century. Earlier discussions of integrating literature in EFL classrooms mainly emphasised the use of literary texts as supplementary materials to ELT coursebooks to reinforce learners’ linguistic knowledge and enhance their understanding of the target language and culture, particularly British and/or American. The current status of ELF challenges the taken-for-granted approaches to selecting and using literary texts in language classrooms, and thus the use of literature in language teaching is in need of rejuvenation. Considering the dynamics and the reality of communication in ELF contexts, language learners today need to be familiarised with the unfamiliar and different ecosystems. The chapter presents literature-based activities designed using two short stories and two novels written by multilingual authors, which can be used with secondary school and university students with B1+ levels of proficiency.